Rechargeable ion battery with polyaniline-based cathode and lean electrolyte

By using a composite of polyaniline and graphene-based material as a cathode active component in sodium ion batteries, and using the reversible embedding/deletion mechanism of cations, the problem of a large number of electrolyte needs is solved, achieving efficient and reversible charging/discharging cycles and low E/C ratios.

CN119908037APending Publication Date: 2025-04-292D POLYMER CELL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202480003913.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-17
Filing Date
2024-03-14
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, when polyaniline is used as the active component of the cathode of sodium ion battery, there is a large demand for electrolytes, resulting in an excessively high electrolyte weight to cathode capacity ratio (E/C), which limits the efficiency and feasibility of the battery.

Method used

A composite of polyaniline and graphene-based materials is used as the cathode active component, and through a new mechanism, utilizing the reversible intercalation/deletion of cations (especially sodium and potassium cations), to achieve electrochemical activity without the need for a large number of anions to participate.

Benefits of technology

The demand for electrolytes is reduced, and a long-term, reversible charging/discharge cycle of polyaniline is achieved. The electrolyte weight to cathode capacity ratio (E/C) is less than 7g/(Ah), which is comparable to commercial lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119908037A_ABST
    Figure CN119908037A_ABST
Patent Text Reader

Abstract

A unique frame for rocking chair type sodium and potassium ion batteries is disclosed. In the case of a sodium ion battery, a battery includes a first electrode operably assembled as an anode of the battery, and includes a sodium ion source. The battery includes a second electrode operably assembled as a cathode of the battery, and includes at least one polymeric binder, an electrically conductive carbon-based material, and an active material. The battery further includes an electrolyte disposed between the first electrode and the second electrode, the electrolyte supporting electrochemical transport of sodium ions. The active material comprises a binary compound, and the binary compound comprises a polyaniline polymer and a graphene-based material. The first electrode, the second electrode, and the electrolyte are operably assembled to function as a rocking chair type sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Citation of Related Applications

[0002] This application claims priority to and the benefit of U.S. Provisional Patent Application No. 63 / 452,748, entitled “SODIUM BATTERIES WITH POLYANILINE BASED CATHODE AND LEANELECTROLYTE,” filed in the U.S. Patent and Trademark Office on March 17, 2023, the contents of which are incorporated by reference in their entirety as if fully set forth herein. Technical Field

[0003] The present disclosure relates to rechargeable metal ion batteries, and in particular to rechargeable metal ion batteries using a composite of polyaniline and a graphene-based material as an active component of a battery cathode. Background Art

[0004] Rechargeable batteries are secondary batteries that can be charged and used multiple times, making them an environmentally friendly and cost-effective alternative to disposable batteries. They are widely used in portable electronic devices (such as smartphones, laptops and cameras) as well as in larger applications (such as electric vehicles and energy storage systems). The most common types of rechargeable batteries are nickel-cadmium batteries, nickel-metal hydride batteries and lithium-ion batteries. Each type of rechargeable battery has its own unique characteristics, including energy density, voltage and discharge rate, making it well suited for different applications. Rechargeable batteries must be properly maintained, including correct storage, correct charging and use within the operating temperature range to ensure their performance and life. Lightweight rechargeable batteries with high energy capacity are the pursuit of autonomous energetics.

[0005] A typical metal-ion battery consists of an anode, a cathode, and an electrolyte that separates the anode from the cathode. The electrolyte is usually a liquid or solid containing metal ions, which act as charge carriers between the anode and cathode. When the battery is charged, these ions move from the cathode to the anode through the electrolyte, and when the battery is discharged, they move in the opposite direction.

[0006] The separator in a battery with a liquid electrolyte acts as a barrier between the anode and cathode, preventing electrical shorts while allowing the flow of metal ions to occur. The separator is typically a porous material, usually made of polypropylene, which is immersed in the electrolyte. It allows the ions to flow while maintaining the structure of the battery. The separator plays a vital role in maintaining the stability and safety of the battery, ensuring that the battery runs smoothly and efficiently.

[0007] Lithium-ion batteries are widely used as autonomous power sources for various portable electronic devices such as mobile phones, cameras, audio equipment, laptop computers, etc., as well as electric and hybrid vehicles and grid systems.

[0008] Sodium-ion batteries have been created as an alternative to lithium-ion batteries. The development of sodium-ion batteries has been driven by the greater availability of sodium precursors for batteries and their lower cost.

[0009] The active material of the anode in a sodium-ion battery generally includes sodium metal, or: sodium alloys of Sn, Sb, Bi, Si, Ge, Si or P; hard or soft carbon materials; materials including graphene; transition metal compounds; or composites based thereon. (I. Hasa et al. Challenges of today for Na-based batteries of the future: From materials to cell metrics. J. Power Sources, 2021, Vol. 482, 228872.).

[0010] The liquid electrolyte is typically composed of a solution of a sodium salt or a mixture of salts in an aprotic organic solvent or a mixture of aprotic organic solvents. Such a liquid electrolyte is typically located within the pores of both the anode and cathode, with a separator, such as a porous polypropylene membrane, between them. The amount and concentration of the liquid electrolyte play a role in providing both the lowest battery weight and the highest level of ionic conductivity.

[0011] For example, the electrochemically active material of the cathode of a sodium-ion battery is one of the most important factors in determining the overall energy storage capacity of the device. The active material of the cathode is typically a material including an inorganic, transition metal-containing cathode material, such as layered sodium oxide, polyanionic compounds, and Prussian blue analogs, which have good application prospects in sodium-ion batteries at the current stage. (Yu.Huang et al., "Electrode Materials ofSodium-Ion Batteries toward Practical Application", ACS Energy Lett., 2018, Vol. 3, P. 1604; I.Hasa et al. Challenges of today for Na-based batteries of the future: From materials to cell metrics. J. Power Sources, 2021, Vol. 482, 228872; Quan Pei et al., "Improving the Na 0.67 Ni 0.33 Mn 0.67O2 Cathode Material for High-Voltage Cyclability via Ti / Cu Codoping for Sodium-Ion Batteries”,ACS Appl. Energy Mater.,2022,Vol.5,P.1953;S.Wang et al.,“Carbon-Modified NASICON Na4FeV(PO4)3 Cathode with Enhanced Kinetics for High-Performance Sodium-Ion Batteries”,ACS Appl. Energy Mater.,2022,Vol.5,P.9616;Wang Hua et al.,“A Preparation Method and Application of Prussian Blue Analogue Cathode Material”,Chinese Patent Application CN115207316A,(2022);S.Xu et al.,“Promising Cathode Materials for Sodium-Ion Batteries from Lab to Application”,ACS Cent. Sci.,2023,Vol.9,P.2012;L.Wang et al. al., "Research Progress and Modification Measures of Anode and Cathode Materials for Sodium-Ion Batteries", ChemElectroChem, 2024, Vol.11, e202300414. )

[0012] However, it is rare to achieve a specific capacity greater than 150 mAh / g using known materials; in addition, harmful degradation reactions using known materials have been shown to affect the structure and composition of the materials, which limits the prospects of high-energy sodium-ion batteries. (G. Brugnetti et al. The Role of Surface Coating in P′2-Na 0.67 Mn 0.67 Ni 0.33 O2: Enhancing Capacity and Stability of Layered Cathodes for Sodium-ion Batteries. Batteries & Supercaps, 2023, e202300332.).

[0013] Other studies have shown that layered Zr-doped Nax Li y M z O a Oxides (where M = Ni, Mn or Co) relative to Na + / Na can have a sufficiently high specific capacity of about 230 mAh / g in the potential range of 1.5-4.3 V, but the presence of Co in the composition leads to greater cost and environmental problems. (KY Chung et al., "Cathode active material for sodium-ion battery, and preparation process thereof" US patent application US2021075053A1 (2021).)

[0014] Due to the anion redox activity, the manganese-based layered cathode achieves a larger specific capacity of about 286 mAh / g, but the relatively low mid-potential value of about 2.5 V and insufficient cyclability reduce the potential of the material for sodium-ion batteries (the specific capacity drops to about 240 mAh / g at the fifth cycle). (Guo Shaohua et al., "A high-energy sodium-ion battery manganese-based layered positive electrode material, preparation method and use", Chinese patent application CN115117336A (2022); Qi Wang et al., "Dual Honeycomb-Superlattice Enables Double-High Activity and Reversibility of Anion Redox for Sodium-Ion Battery Layered Cathodes", Angew. Chem., 2022, Vol. 134, e202206625.).

[0015] Some organic materials have been used as alternatives to inorganic cathode materials. (X. Yin et al., "Recent Progress in Advanced Organic Electrode Materials for Sodium-Ion Batteries: Synthesis, Mechanisms, Challenges and Perspectives", Adv. Funct. Mater., 2020, Vol. 30, 1908445; R. Rajagopalan et al., "Understanding the sodium storage mechanisms of organic electrodes in sodium ion batteries: issues and solutions", Energy Environ. Sci., 2020, Vol. 13, P. 1568.) The characteristic property of these organic materials is the presence of carbon-containing and heteroatom-containing groups that can undergo reversible electrochemical transformations. When their discharge potential is large enough, the specific capacity of these materials is rarely higher than 150 mAh / g, and when their discharge potential is low enough, the discharge capacity of these materials can be quite large. Therefore, high-energy sodium-ion batteries utilizing organic cathode materials remain an unsolved challenge in rechargeable battery research and development. Furthermore, in some cases, organic materials are only suitable for use in dual-ion batteries because their electrochemical activity is accompanied by the insertion / extraction of anions present in the battery electrolyte.

[0016] For example, polybenzothiazolyl-based cathode materials can be + / Na shows a specific capacity of about 150mAh / g in the potential range of 1.5-4.0V. (Wang Gang et al., "Sulfonated polybenzothiazolyl-based cathode material for sodium ion batteries and preparation method thereof", Chinese patent application CN114975999A (2022).) In another example, the ladder-type hexaazatriphenylene polymer has a specific capacity of about 150mAh / g in the potential range of 1.5-4.0V relative to Na + / Na in the potential range of 0.9-3.5V, it exhibits a specific capacity of 170-180mAh / g at a discharge current of 100mA / g, but its mid-potential is relatively low relative to Na + / Na is only about 2V. (RRKapaev et al., "ConjugatedLadder-Type Polymer with Hexaazatriphenylene Units as a Cathode Material forLithium,Sodium,and Potassium Batteries", ACS Appl.Energy Mater., 2021, Vol.4, P.10423.) In addition, the modified pyrene-based polymer has a low relative humidity and low temperature. + / Na shows a specific capacity of about 360 mAh / g in the potential range of 1.0-3.5 V, but its mid-potential is relatively + / Na is also about 2V, and the relatively low polymer content in the cathode material does not support the preparation of high-energy batteries based on it. (R. Shi et al., "In Situ Polymerized Conjugated Poly (pyrene-4,5,9,10-tetraone) / Carbon Nanotubes Composites for High-Performance Cathode of Sodium Batteries", Adv. Energy Mater., 2021, Vol. 11, 2002917.).

[0017] Organic polymer polyaniline itself has been used as an active component of the cathode of sodium battery. Due to the system of conjugated bonds, polyaniline has redox activity, can have conductivity by doping and can undergo reverse electrochemical transformation at high potential. These characteristics have inspired the possibility of using polyaniline as an active component of the cathode of sodium ion batteries. For example, self-doped polyaniline has been used as a component of the cathode of sodium ion batteries, and its reversible specific capacity at a specific discharge current of 50mA / g is about 100mAh / g. (YFShen et al., "Poly (diphenylaminesulfonic acid sodium) as acation-exchange organic cathode for sodium batteries", Electrochem. Commun., 2014, Vol. 49, P. 5.). In another study, self-doped polyaniline showed a capacity of about 133mAh / g and exhibited high cyclability. (M.Zhou et al.,A sulfonated polyaniline with high density and highrate Na-storage performances as a flexible organic cathode for sodium-ion batteries.Chem.Commun.,2015,51,14354-14356.). Polyaniline hollow nanofibers have been used as cathode materials for sodium-ion batteries, showing a reversible capacity of 153mAh / g. (H.Han et al.,Polyaniline hollownanofibers prepared by controllable sacrifice template route as high-performance cathode materials for sodium-ion batteries.Electrochim.Acta 2019,Vol.301,352-358.). Finally, hybrid nanocomposites based on transition metal hexacyanoferrates and polyaniline exhibited a specific discharge capacity of up to 150mAh / g in the cathode of sodium batteries.(Q. Zhang et al., "Surface engineering induced core-shell Prussian blue@polyaniline nanocubes as a high-rate and long-life sodium-ion battery cathode", J. Power Sources, 2018, Vol. 395, P. 305.).

[0018] However, the specific capacity at or below the common 50% doping limit of polyaniline (about 150 mAh / g) is relatively low for an efficient cathode to be used in a sodium battery. + / NaThe electrochemical activity at potentials above 1.7V is believed to be due to the insertion / extraction of sodium cations, while for ordinary polyaniline (non-self-doped), the electrochemical activity within the above potential range is believed to be due to the insertion / extraction of anions present in the electrolyte. Therefore, polyaniline polymers are actually only suitable for cathodes of dual-ion batteries. (M.Zhou et al.Asulfonated polyaniline with high density and high rate Na-storageperformances as a flexible organic cathode for sodium-ionbatteries.Chem.Commun.,2015,51,14354-14356;H.Han et al.,Polyaniline hollownanofibers prepared by controllable sacrifice template route as high-performance cathode materials for sodium-ion batteries.Electrochim.Acta 2019,Vol.301,352-358.).

[0019] Recently, a specific capacity of about 175 mAh / g was shown in lithium-ion batteries, corresponding to polyaniline doping above the 50% limit. (J. Gaubicher et al., "Lithium-Doped Pernigraniline-Based Materials", International Patent Application Serial No. PCT / EP2015 / 053689.) Composites of polyaniline with graphene-based materials exhibit significantly greater specific capacities, about 250 mAh / g. (O. Posudiievskyi, International Patent Application Serial No. PCT / IB2018 / 055009.) However, it should be noted that there is no evidence that polyaniline has a practical high specific capacity and long charge / discharge cycles in sodium-ion batteries.

[0020] The minimum amount of anions required to 100% dope polyaniline is considered to be equal to one anion per nitrogen atom of the polymer, or 1 mole of anions per about 91 grams of polymer (C6H4NH is generally considered to be the unit cell of polyaniline), or 1L of a common liquid organic electrolyte with an alkali metal salt concentration of 1M per about 91 grams of polymer. (Y. Yamada et al., "Advances and issues in developing salt concentrated battery electrolytes", Nat. Energy, 2019, Vol. 4, p. 269; Z. Guo et al., "Toward Full Utilization and Stable Cycling of Polyaniline Cathode for Nonaqueous Rechargeable Batteries", Adv. Energy Mater., 2023, Vol. 13, 2301520.)

[0021] Therefore, in theory, about 11 mL of electrolyte is required for every about 1 gram of polymer in the cathode material, or about 15 grams of electrolyte for every 294 mAh of charge, which is the theoretical charge storage limit of the polymer. Therefore, the electrolyte weight to cathode capacity ratio (E / C) in such a battery is about 50 g / (Ah). This very high E / C value indicates that dual-ion batteries with polyaniline-based cathodes are severely limited, if not practically unfeasible. In fact, practical lithium-ion batteries exhibit E / C ratios below 3 g / (Ah). (X.Ren et al., "Enabling High-Voltage Lithium-Metal Batteries underPractical Conditions", Joule, 2019, Vol.3, p.1662; Sh.Chen et al., "CriticalParameters for Evaluating Coin Cells and Pouch Cells of Rechargeable Li-MetalBatteries",Joule,2019,Vol.3,p.1094; J.Liu et al.,"Pathways for practical high-energy long-cycling lithium metal batteries",Nat.Energy,2019,Vol.4,p.180;H.Li.,"Practical Evaluation of Li-Ion Batteries",Joule,2019,Vol.3,p.911.)

[0022] Potassium-ion batteries have been created as another alternative to lithium-ion batteries. The development of potassium-ion batteries is driven by the greater availability of potassium precursors for batteries and their lower cost compared to lithium, as well as the lower redox potential of potassium compared to sodium, the much smaller Stokes radius of K+ ions compared to Li+ and Na+ ions, the use of aluminum foil instead of copper foil as a current collector for the anode, and the applicability of graphite as an active anode material. (K. Sada et al., "Challenges and Prospects of Sodium-Ion and Potassium-Ion Batteries for Mass Production", Adv. Energy Mater., 2023, Vol. 13, 2302321; Yan-Song Xu et al., "High-Performance Cathode Materials for Potassium-Ion Batteries: Structural Design and Electrochemical Properties", Adv. Mater. 2021, Vol. 33, 2100409.) Summary of the invention

[0023] In general, a system and method are disclosed that provide a new mechanism for the charge / discharge process of polyaniline, without the involvement of anions, and also based on the reversible insertion / extraction of cations (particularly sodium and potassium cations). The disclosed system and method solve the problem of the large amount of electrolyte required for polyaniline to function as an electrochemically active component of the cathode of a rechargeable metal ion battery (particularly a sodium ion battery and a potassium ion battery), while providing a long, reversible charge / discharge cycle of polyaniline. The method has many positive implications for the cathode of practical rechargeable sodium ion batteries and potassium ion batteries.

[0024] It should be understood that while the present disclosure presents a novel battery model utilizing sodium as the mobile cation, other embodiments are also contemplated where the cation is a different species (eg, but not limited to, potassium).

[0025] The systems and methods disclosed herein provide the possibility of rocking chair-like operation of fixed electrolyte batteries using polyaniline as the cathode active component. The practical advantage of constant electrolyte concentration is that the metal ion conductivity between the battery electrodes is maximized due to the filling of the electrode pores, resulting in efficient metal ion transport. The minimum amount of electrolyte sufficient to fill the separator and electrode pores provides an E / C ratio of less than 7 g / (Ah), which is comparable to the best-known commercial lithium-ion batteries.

[0026] In a first general aspect, a sodium ion battery comprises: a first electrode operably assembled as an anode of the battery, which provides a source of sodium ions; a second electrode operably assembled as a cathode of the battery, which comprises at least one polymer binder, a conductive carbon-based material, and an active material; and an electrolyte disposed between the first electrode and the second electrode, which supports electrochemical transport of sodium ions. The active material comprises a binary composite comprising: 1) a polyaniline polymer, and 2) a graphene-based material. The first electrode, the second electrode, and the electrolyte are operably assembled to function as a rocking chair type sodium ion battery.

[0027] In one embodiment, the battery further comprises an insulating porous membrane disposed between the first electrode and the second electrode. In this embodiment, the electrolyte is a liquid electrolyte comprising at least one aprotic solvent and at least one sodium salt soluble in the at least one aprotic solvent. Alternatively, the liquid electrolyte comprises at least one ionic liquid comprising at least one sodium salt soluble in the at least one ionic liquid. In this embodiment, the insulating porous membrane is immersed in the electrolyte, and the amount of electrolyte in the battery, expressed as a ratio of electrolyte weight to cathode capacity, is less than 7 g / (Ah).

[0028] In one embodiment, the electrolyte of the battery is a sodium ion conducting solid. The solid includes: a sodium ion conducting organic polymer; a sodium ion conducting inorganic compound; a sodium ion conducting ion gel; or a composite material comprising a sodium ion conducting organic polymer, a sodium ion conducting inorganic compound, a sodium ion conducting ion gel or a combination thereof.

[0029] In a second general aspect, a potassium ion battery comprises: a first electrode operably assembled as an anode of the battery, which provides a source of potassium ions; a second electrode operably assembled as a cathode of the battery, which comprises at least one polymer binder, a conductive carbon-based material, and an active material; and an electrolyte disposed between the first electrode and the second electrode, which supports electrochemical transport of potassium ions. The active material comprises a binary composite comprising a polyaniline polymer and a graphene-based material. The first electrode, the second electrode, and the electrolyte are operably assembled to function as a rocking chair type potassium ion battery.

[0030] In one embodiment of the second general aspect, the battery further comprises an insulating porous membrane disposed between the first electrode and the second electrode. In this embodiment, the electrolyte is a liquid electrolyte comprising at least one aprotic solvent and at least one potassium salt soluble in the at least one aprotic solvent and at least one ionic liquid, the at least one ionic liquid comprising at least one potassium salt soluble in the at least one ionic liquid. The insulating porous membrane is immersed in the electrolyte. The amount of electrolyte in the battery, expressed as a ratio of electrolyte weight to cathode capacity, is less than 7 g / (Ah).

[0031] In another embodiment of the second general aspect, the electrolyte of the battery is a potassium ion conducting solid including a potassium ion conducting organic polymer, a potassium ion conducting inorganic compound, a potassium ion conducting ion gel, or a composite material including a potassium ion conducting organic polymer, a potassium ion conducting inorganic compound, a potassium ion conducting ion gel, or a combination thereof.

[0032] In a third general aspect, a method of making a metal ion battery is provided. The method includes providing a first electrode including a source of metal ions and operably assembling the first electrode as an anode of the battery, providing a second electrode and operably assembling the second electrode as a cathode of the battery. The second electrode includes at least one polymer binder, a conductive carbon-based material, and an active material. The method further includes providing an electrolyte between the first electrode and the second electrode, the electrolyte supporting electrochemical transport of metal ions between the first electrode and the second electrode. The active material includes a binary composite, the binary composite including polyaniline and a graphene-based material.

[0033] In one embodiment of the third general aspect, the metal is sodium or potassium.

[0034] In one embodiment of the third general aspect, a binary composite of polyaniline and graphene-based materials is prepared according to a method comprising grinding a mixture of polyaniline and graphene-based materials in eigenstate form. In a related embodiment, grinding is performed in a solvent-free environment. In another related embodiment, the graphene-based material comprises a mixture of multilayer, small amount of layers and monolayer graphene particles. In another related embodiment, the mixture is prepared by chemical, mechanochemical, electrochemical, sonochemical or thermochemical exfoliation of particles of graphite, graphene oxide, intercalated graphite or expanded graphite. The mixture of polyaniline and graphene-based materials in eigenstate form can be prepared using polyaniline and graphene-based materials in a relative weight ratio of about 75:25 to about 99:1. The method may include an optional step of separating and purifying the composite of polyaniline and graphene-based materials.

[0035] In another embodiment of the third general aspect, the second electrode is formed by a deposition step comprising depositing a cathode material onto a current collector, the cathode material comprising a binder, a conductive additive, and an active material. In a related embodiment, the binder is water soluble. In addition, the deposition step may include preparing a slurry of the cathode material by mixing the binder, the conductive additive, and the active material with water. The binder is soluble in a polar organic solvent. In a related embodiment, the deposition step includes preparing a slurry of the cathode material by mixing the binder, the conductive additive, and the active material with a polar organic solvent. In a related embodiment, the method includes using a slurry that does not contain N-methylpyrrolidone.

[0036] Unless otherwise limited, all technical and scientific terms used herein have the same meaning as those of ordinary skill in the art generally understand. Although methods and materials similar to or equal to those methods and materials described herein can be used in the practice or test of any described embodiment, suitable methods and materials are described below. In addition, materials, methods and examples are only illustrative and are not intended to be limited. In the case of conflict with the term used in this area, this specification (including definition) shall prevail.

[0037] The foregoing summary is illustrative only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments, and features described above, further aspects, embodiments, and features will become apparent by reference to the drawings and the following detailed description and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The present embodiments are illustrated by the figures of the accompanying drawings, which are not necessarily drawn to scale, in which like reference numerals represent similar elements, and in which:

[0039] Figure 1 shows a cross section of a rechargeable battery using a polyaniline-based cathode according to one embodiment;

[0040] Figure 2 is a graph plotting specific capacity versus cycle number for a first battery cell and a second battery cell according to the present disclosure;

[0041] Figure 3 is a graph plotting specific capacity versus cycle number for a third battery cell according to the present disclosure;

[0042] Figure 4 is a graph plotting the potential of the third battery cell versus the discharge capacity;

[0043] Figure 5 is a graph plotting specific capacity versus cycle number for a fourth battery cell according to the present disclosure; and

[0044] Figure 6 is a graph plotting specific capacity versus cycle number for a fifth battery cell according to the present disclosure. DETAILED DESCRIPTION

[0045] Figure 1is a schematic cross-section of a rechargeable battery 1 according to one embodiment. In this embodiment, the active component of the battery cathode is a binary composite of: 1) polyaniline; and 2) graphene-based material. In this embodiment, the rechargeable battery 1 includes an anode layer 2, an electrolyte layer 3, and a cathode layer 4. In this embodiment, the anode layer 2 is composed of sodium or a sodium alloy, a composite including sodium, or other anode materials, but is not limited thereto. The anode layer 2 may alternatively be composed of materials such as, but not limited to, hard carbon materials, graphene materials, transition metal-based compounds, or any combination thereof as active components. It should be understood that the sodiumized form of hard carbon, graphene, or transition metal-based materials can be used for optimal battery performance.

[0046] In this embodiment, the electrolyte layer 3 can be: 1) a porous polymer membrane immersed in a liquid electrolyte, which is a solution of one sodium salt or several sodium salts in an organic aprotic solvent or a mixture of different aprotic solvents, preferably including additives for improving the electrode-electrolyte interface; 2) a porous separator immersed in an ionic liquid electrolyte, which is a solution of one sodium salt or several sodium salts in an ionic liquid or a mixture of different ionic liquids; 3) a sodium ion conducting solid electrolyte layer, which includes an organic polymer membrane having the ability to conduct sodium ions alone or in combination with a corresponding sodium salt; 4) a sodium ion conducting inorganic solid; 5) a composite thereof; or 6) a solid ion gel electrolyte.

[0047] In this embodiment, the cathode layer 4 contains a binary composite (hereinafter referred to as "PANI / GBM") of the following items as active components: 1) polyaniline and 2) a graphene-based material, which is disclosed in International Patent Application Serial No. PCT / IB2018 / 055009 (which is incorporated herein by reference in its entirety). The PANI / GBM composite can be prepared by a solvent-free mechanochemical method, including mechanochemical treatment of a mixture of polyaniline in an eigenstate form and a mixture of multilayer, few-layer and monolayer graphene particles as GBM. The mechanochemical method for preparing the PANI / GBM composite is similar to the mechanochemical method for preparing hybrid nanocomposites disclosed in O. Posudievsky et al., "Hybrid Two-and Three-Component Host-Guest Nanocomposites and Method for Manufacturing the Same", and U.S. Patent Application Serial No. 12 / 623,000 assigned to General Motors (GM Global Technology Operations, Inc.), which is incorporated herein by reference in its entirety.

[0048] In this example, a rechargeable battery 1 is shown to exhibit rocking chair functionality (i.e., sodium cation insertion / extraction induced charge / discharge cycles) utilizing: a sodium metal anode, an electrolyte layer, and a PANI / GBM composite-based cathode. The rechargeable battery 1 was assembled in a Swagelok cell in an argon-filled MBRAUN glove box with oxygen and water content below 0.1 ppm.

[0049] In order to study the characteristics of the rechargeable battery 1, several battery cells were manufactured. The first battery cell ("battery cell 1") includes a cathode material formed by a PANI / GBM composite (polyaniline to GBM weight ratio equal to about 9: 1) prepared by mechanochemical according to the procedure described in International Patent Application Serial No. PCT / IB2018 / 055009, a polymer binder and a carbon black additive. International Patent Application Serial No. PCT / IB2018 / 055009 is incorporated herein by reference. The weight ratio of the cathode material components is 85: 10: 5 (PANI / GBM composite: polymer binder: carbon black additive). In this example, the polymer binder is a poly [(vinylidene fluoride)-co-hexafluoropropylene] copolymer, and acetone is used as a solvent for preparing a slurry, which is used to deposit a PANI / GBM composite-based cathode material on a cathode collector using a scraper. The cathode material is loaded to ensure that the single-sided area capacity is about 2 mAh / cm 2 To demonstrate the rocking chair functionality (e.g., cation insertion / extraction induced charge / discharge cycling), cell 1 utilized an anode made of bulk sodium metal, 5.5 mg of cathode material, and an electrolyte layer consisting of a Celgard 2400 polypropylene membrane (Celgard, LLC, Charlotte, NC, USA) immersed in an ethylene carbonate-diethyl carbonate mixture (50:50 volume ratio) containing 0.42 mg of NaClO4 salt sufficient to ensure that the doping level of polyaniline present in the cathode material was only 10%.

[0050] The second cell ("Cell II") was prepared in a similar procedure to Cell I, except that pure intrinsic form of polyaniline was used as the active material for the cathode material instead of the PANI / GBM composite in Cell I.

[0051] The third cell ("Cell III") was prepared in a similar procedure to the Cell I sample, except that the separator was immersed in a 1 M NaClO4 solution in an ethylene carbonate-diethyl carbonate mixture (50:50 volume ratio).

[0052] The fourth cell ("Cell IV") was prepared in a similar procedure to Cell III, except that polyvinylidene fluoride binder and N-methyl-2-pyrrolidone (NMP) were used as solvent during the preparation of the slurry for depositing the PANI / GBM-based cathode material on the cathode current collector.

[0053] The fifth cell ("Cell V") was prepared in a similar procedure to the Cell III sample, except that the polymer binder was a mixture of polyolefin grafted acrylic copolymer (3 wt% aqueous solution) and carboxymethyl cellulose (2.5 wt% aqueous solution) in a ratio of 1:3. In this example, the cathode material slurry was prepared using double distilled water and the slurry was deposited on the cathode current collector using a doctor blade. The cathode material was dried at 60°C in air and then dried at 80°C under vacuum.

[0054] In all cases, the specific capacity was calculated using the polyaniline content in the cathode material. + The cycle was performed in the potential range of 1.7-4.1 V for Na / Na. The charge and discharge currents were both equal to 15 mA / g. The specific current value was calculated using the total weight of the cathode material.

[0055] Reference now Figure 2 , the cycling data show that the discharge specific capacity of polyaniline in battery cell I increases. Figure 2 The ability of polyaniline to sustain charge / discharge cycles in the absence of a sufficient number of mobile anions in the electrolyte (1 / 10 of the amount required for a theoretical 100% doping level) is demonstrated, as well as its ability to reach about 60% of its theoretical specific capacity of 294 mAh / g at the fifth cycle. This means that the capacity of polyaniline at this cycle is about 6 times higher than the maximum theoretical value that can be used for anion doping of polyaniline due to the particularly limited sodium salt content in the electrolyte of battery cell I. Without wishing to be bound by theory, it is assumed that the steady increase in the specific capacity of polyaniline is due to the gradual sodiumization of nitrogen atoms within its structure, because the doping / dedoping of polyaniline in battery cell I to this extent during cycling can only be carried out with the participation of mobile sodium cations.

[0056] Figure 2 It is further illustrated that the effective functioning of polyaniline as the active component of the cathode in battery cell I is due to the presence of GBM and its effect on polyaniline, because in the absence of GBM particles (and therefore in the absence of interaction between GBM particles and polyaniline macromolecules), due to the amount of mobile anions in the electrolyte of battery cell II, the specific capacity of polyaniline in battery cell II without GBM in the composition of the cathode material only reaches about 1 / 23 of its maximum theoretical doping level (i.e., more than twice lower than the theoretical limit of 10%).

[0057] Reference now Figure 3 , shows the charge and discharge cycle data of battery cell III. The polyaniline in battery cell III is characterized by a high specific capacity of about 260 mAh / g. In addition, Figure 4 The PANI / GBM composite in cell III is shown to be characterized by relative + / Na is a high mid-potential of about 3.04 V. In an optional embodiment, it is envisioned that a small amount of sodium salt can be dissolved in an organic aprotic solvent as a component of the electrolyte to simultaneously ensure low battery weight and provide the necessary level of ionic conductivity. These data show that polyaniline-based sodium-ion batteries with lean electrolytes and weight-to-capacity ratios below 5 g / (Ah) can perform as well as known commercial lithium-ion batteries.

[0058] Reference now Figure 5 , showing the charge and discharge cycle data of battery cell IV. From these data, it is obvious that the use of binders such as polyvinylidene fluoride and solvents such as (N-methylpyrrolidone) is contraindicated for preparing PANI / GBM cathode material slurry and depositing the cathode material on the cathode collector during the production of battery cell IV, due to the partial dissolution of polyaniline by N-methylpyrrolidone. The dissolution of polyaniline destroys the interaction between polyaniline and GBM, which in turn eliminates the conduction of new polyaniline doping mechanisms and limits its specific capacity in battery cell IV to a value of 50% doping.

[0059] Reference now Figure 6 , shows the charge and discharge cycle data of battery cell V. Figure 6 It is shown that aqueous solutions of water-soluble binders such as polyacrylic acid and carboxymethyl cellulose can be used to prepare cathode material slurries to provide lower costs for cathode material preparation and processing and reduce the use of organic solvents that cause ecological and environmental hazards associated with battery manufacturing.

[0060] Electrochemically active organic electrode materials are characterized by ionic universality. In related and similar embodiments, rocking chair potassium ion batteries can be produced using PANI / GBM composites as the active material for the cathode. Importantly, in specific organic solvents, K + / K potential can be lower than Na + / Na potential, even lower than Li + / Li potential, which is useful for increasing energy density. Similar to sodium-ion batteries, potassium ions do not form alloys with aluminum when aluminum foil is used as the anode current collector. In contrast to sodium ions, potassium ions can be intercalated in graphite with high capacity. Compared with lithium and sodium ions, potassium ions can exhibit significantly weaker Lewis acidity and smaller Stokes radius in organic solvents, indicating that increased ion mobility across the bulk electrolyte and electrolyte / electrode interface is beneficial for achieving high power density.

[0061] The radius of the potassium ion Larger than the radius of a sodium ion Therefore, using conventional inorganic electrode materials for potassium-ion batteries may lead to considerable structural deformation, resulting in lower capacity and rapid capacity decay. In contrast, organic electrode materials assembled due to specific van der Waals forces usually have large interlayer spacing and flexible structures.

[0062] However, it has been shown that if the average voltage of potassium ion batteries with cathodes based on electrochemically active materials is mostly below 3V, the capacity of these materials is rarely greater than 150 mAh / g. (X. Zhu et al. Recent Advances in Polymers for Potassium Ion Batteries. Polymers, 2022, 14, 5538; M. Wang et al. Organic Electrode Materials for Non-aqueous K-Ion Batteries. Trans. Tianjin University, 2021, Vol. 27, 1–23; S. Liu et al. Challenges and Strategies toward Cathode Materials for Rechargeable Potassium-Ion Batteries. Adv. Mater. 2021, Vol. 33, 2004689; Lin Li et al. Cathode materials for high-performance potassium-ion batteries. Cell Reports Physical Science 2, 100657.).

[0063] In particular, it has been shown that polyaniline can be used as an electrochemically active material for the cathode of a potassium ion battery; however, although the average voltage of the battery is about 3V, the polyaniline capacity is less than 150mAh / g. In addition, in this case, the electrochemical activity of polyaniline is due to the insertion / extraction of anions, so the disclosed battery is a dual-ion battery potassium battery. (H.Gao et al.A High-Energy-Density Potassium Battery with a Polymer-Gel Electrolyte and a Polyaniline Cathode.Angew.Chem.Int.Ed.2018,Vol.57,5449–5453.).

[0064] A number of illustrative embodiments have been described. However, it should be understood that various modifications may be made without departing from the spirit and scope of the various embodiments presented herein. Therefore, other embodiments are within the scope of the following claims.

Claims

1. A sodium ion battery comprising: a first electrode operably assembled as an anode of the cell and comprising a source of sodium ions; a second electrode operable to assemble as a cathode of the cell and comprising at least one polymer binder, a conductive carbon-based material, and an active material; as well as an electrolyte disposed between the first electrode and the second electrode, the electrolyte supporting electrochemical transport of the sodium ions; wherein the active material comprises a binary composite comprising: 1) a polyaniline polymer, and 2) a graphene-based material; and The first electrode, the second electrode and the electrolyte are operably assembled to function as a rocking-chair type sodium ion battery.

2. The battery according to claim 1, further comprising an insulating porous separator disposed between the first electrode and the second electrode; wherein the electrolyte is a liquid electrolyte comprising: at least one aprotic solvent and at least one sodium salt soluble in the at least one aprotic solvent; or at least one ionic liquid comprising at least one sodium salt soluble in the at least one ionic liquid; and wherein the insulating porous separator is immersed in the electrolyte; and The amount of the electrolyte in the battery, expressed as a ratio of electrolyte weight to cathode capacity, is less than 7 g / (Ah).

3. The battery of claim 1, wherein the electrolyte is a sodium ion conducting solid comprising: Sodium ion conducting organic polymers; Sodium ion conducting inorganic compounds; a sodium ion conducting ion gel; or A composite material comprising the sodium ion conducting organic polymer, the sodium ion conducting inorganic compound, the sodium ion conducting ion gel or a combination thereof.

4. A potassium ion battery comprising: a first electrode operably assembled to serve as an anode of the cell and comprising a source of potassium ions; a second electrode operable to assemble as a cathode of the cell and comprising at least one polymer binder, a conductive carbon-based material, and an active material; as well as an electrolyte disposed between the first electrode and the second electrode, the electrolyte supporting electrochemical transport of the potassium ions; wherein the active material comprises a binary composite comprising: 1) a polyaniline polymer, and 2) a graphene-based material; and The first electrode, the second electrode and the electrolyte are operably assembled to function as a rocking-chair type potassium ion battery.

5. The battery according to claim 4, further comprising an insulating porous separator disposed between the first electrode and the second electrode; wherein the electrolyte is a liquid electrolyte comprising: at least one aprotic solvent and at least one potassium salt soluble in the at least one aprotic solvent; at least one ionic liquid comprising at least one potassium salt soluble in the at least one ionic liquid; and wherein the insulating porous separator is immersed in the electrolyte; and The amount of the electrolyte in the battery, expressed as a ratio of electrolyte weight to cathode capacity, is less than 7 g / (Ah).

6. The battery of claim 4, wherein the electrolyte is a potassium ion conducting solid comprising: Potassium ion conducting organic polymers; Potassium ion conducting inorganic compounds; Potassium ion conducting ion gel; or A composite material comprising the potassium ion conducting organic polymer, the potassium ion conducting inorganic compound, the potassium ion conducting ion gel or a combination thereof.

7. A method for manufacturing a metal ion battery, comprising: providing a first electrode comprising a source of metal ions and operably assembling the first electrode as an anode of the cell; providing a second electrode and operably assembling the second electrode as a cathode of the battery, wherein the second electrode comprises at least one polymer binder, a conductive carbon-based material, and an active material; providing an electrolyte between the first electrode and the second electrode, the electrolyte supporting electrochemical transport of metal ions between the first electrode and the second electrode; The active material comprises a binary composite comprising polyaniline and a graphene-based material.

8. The method of claim 7, wherein the metal is sodium or potassium.

9. The method of claim 7, wherein the binary composite of polyaniline and a graphene-based material is prepared according to a method comprising milling a mixture of polyaniline in an eigenstate form and a graphene-based material.

10. The method of claim 9, wherein the grinding is performed in a solvent-free environment.

11. The method of claim 9, wherein the graphene-based material comprises a mixture of multi-layer, few-layer, and single-layer graphene particles.

12. The method of claim 11, wherein the mixture is prepared by chemical, mechanochemical, electrochemical, sonochemical or thermochemical exfoliation of particles of graphite, graphene oxide, intercalated graphite or expanded graphite.

13. The method of claim 9, wherein the mixture of polyaniline in an eigenstate form and a graphene-based material is prepared using a relative weight ratio of polyaniline to graphene-based material between about 75:25 and about 99:

1.

14. The method of claim 9, further comprising the optional step of isolating and purifying the composite of polyaniline and graphene-based material.

15. The method of claim 7, wherein the second electrode is formed by a deposition step comprising depositing a cathode mass onto a current collector, the cathode mass comprising a binder, a conductive additive, and the active material.

16. The method of claim 15, wherein the binder is water soluble.

17. The method of claim 16, wherein the depositing step comprises preparing a slurry of the cathode material by mixing the binder, the conductive additive, and the active material with water.

18. The method of claim 15, wherein the binder is soluble in a polar organic solvent.

19. The method of claim 18, wherein the depositing step comprises preparing a slurry of the cathode material by mixing the binder, the conductive additive, and the active material with a polar organic solvent.

20. The method of claim 19, wherein the slurry is free of N-methylpyrrolidone.

Citation Information

Patent Citations

  • Sulfonated polybenzothiazole-based cathode material for sodium ion battery and preparation method of sulfonated polybenzothiazole-based cathode material

    CN114975999A

  • Manganese-based layered positive electrode material for high-specific-energy sodium-ion battery, and preparation method and application of manganese-based layered positive electrode material

    CN115117336A

  • Preparation method and application of Prussian blue analogue positive electrode material

    CN115207316A

  • Hybrid two- and three-component host-guest nanocomposites and method for manufacturing the same

    US20110121225A1

  • Cathode active material for sodium ion battery, and preparation process thereof

    US20210075053A1